2021
DOI: 10.1007/s12144-021-02317-y
|View full text |Cite
|
Sign up to set email alerts
|

The influence of job crafting on the quality of care provided by nursing home employees: The moderating effect of organizational identification

Abstract: Our goal was to analyze the positive effect of job crafting activities involving nursing home employees on their perceived quality of care, and the moderating effect of organizational identification. A two-wave non-experimental design (with an interval of 12 months) was used. The Job Crafting Questionnaire, the Identification-Commitment Inventory, and the Quality of Care Questionnaire (QoC) were administered to 226 nursing home employees in two waves. The results of the hierarchical regression analyses found s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 72 publications
0
3
0
Order By: Relevance
“…Generally, nurses have a unique role in modern medicine [26]. However, nurses' poor work conditions have deleterious consequences, putting the safekeeping and qualityof-care standards at risk [27]. Terefore, nursing scholars become more interested in studying job crafting [11], and others recommend interventions to foster it among nurses because of the urgent concern and the belief that it is a powerful strategy that can change their work environment positively [13].…”
Section: Introductionmentioning
confidence: 99%
“…Generally, nurses have a unique role in modern medicine [26]. However, nurses' poor work conditions have deleterious consequences, putting the safekeeping and qualityof-care standards at risk [27]. Terefore, nursing scholars become more interested in studying job crafting [11], and others recommend interventions to foster it among nurses because of the urgent concern and the belief that it is a powerful strategy that can change their work environment positively [13].…”
Section: Introductionmentioning
confidence: 99%
“…Lichtenthaler and Fischbach defined job crafting as employee-driven modifications in concrete work role bounds and intangible work role perceptions [ 3 ]. Through this process, employees can enhance their work identities by recognizing the meaning of their work, growing and shrinking various relational aspects of their jobs, and modifying (i.e., increasing or decreasing) the number, scope, or nature of job tasks performed [ 4 ]. Romeo et al noted that initiating changes in duties and interactions or even adjusting beliefs about the work is an example of job crafting, the active behavior that gives workers the opportunity to redesign their work environment [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Baghdadi et al (2020) found that job crafting accounted for 57% of the variance in work engagement among nurses. Romeo et al (2021) reported that job crafting (task, relational, and cognitive) is positively related to the quality of care in residential homes for the elderly. Gordon et al (2018) concluded from their intervention study that job crafting influences well-being (i.e., work engagement, health, and reduced exhaustion), and job performance (i.e., adaptive, task, and contextual performance).…”
Section: Introductionmentioning
confidence: 99%